Sepsis-Induced Coagulopathy and Disseminated Intravascular Coagulation - Iba, Toshiaki; Levi, Marcel; Levy, Jerrold H (Seminars in thrombosis and hemostasis, 2020)
Disseminated intravascular coagulation (DIC) has been recognized as a deadly complication in sepsis, and its early recognition followed by appropriate management of the underlying infection are the current management strategies. The activation of coagulation, inflammation, and other pathways are fundamental host responses against infection but also produce injury to the host. Recent advances have helped define the critical roles of thrombus formation in overcoming infection. In addition to activation of coagulation induced by pathogens, other important pathways including damage-associated molecular patterns, neutrophil extracellular traps, extracellular vesicles, and glycocalyx damage are involved in the pathogenesis of sepsis-induced DIC. The hallmark of DIC is thrombosis in the microvasculature; however, sepsis-induced DIC is a laboratory diagnosis based on coagulation test results and clinical setting. Although simplified criteria were recently introduced, DIC should be distinguished from other similar conditions such as thrombotic microangiopathy and heparin-induced thrombocytopenia. In DIC, treating the underlying cause is crucial, and additional adjunct therapies including antithrombin, thrombomodulin, and heparins may have potential benefit, but evidence supporting their use in terms of improvement of clinically relevant outcomes continues to be debated. In this review, we introduce recent findings regarding the pathophysiology, diagnosis, and treatment of sepsis-induced DIC. In addition, we also discuss future potential therapeutic approaches regarding this complex, life-threatening complication.